The Washington manual gastroenterology subspecialty consult - Gyawali, C. Prakash; Ciesielski, Thomas (Washington manual subspecialty consult series., 2021)
"Advances in the field of gastroenterology since the last edition of this manual have been incorporated into the chapters in this edition. The manual continues to provide succinct, precise recommendations on the evaluation and management of common gastrointestinal symptoms and disorders. Each chapter has been thoroughly revised, and some chapters have been rewritten, to update content to modern concepts and guidelines. The chapters were written predominantly by Washington University subspecialty fellows, with support and guidance from their faculty mentors. Similar to previous editions, the fourth edition of the manual is targeted to medical students, novice and advanced trainees, physician extenders, nurse practitioners, other health care providers, and physicians, and will provide easy access to clinically relevant recommendations for diagnosis and management of gastrointestinal disorders"--